The relationship of formal reasoning ability and achievement motivation with student learning achievement - Sappaile, Baso Intang; Abeng, Andi Tenri; Nuridayanti, Nuridayanti (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
The purpose of this study was to determine the relationship between formal reasoning abilities and student achievement motivation. The method used is a quantitative research method with analysis using product moment correlation, assisted by SPSS version 16. Correlation research is a type of research used to explore the relationship between two or more variables. This study aims to determine whether there is a statistical relationship between these variables and to what extent this relationship is correlated. As for this study, researchers used the help of SPSS version 16 in analyzing the data. The sample selection in this study used a random sampling of 30 students. The independent variables in this study are formal reasoning (X1) and achievement motivation (X2), and the dependent variable is learning achievement (Y). Collecting data on formal reasoning, achievement motivation, and student achievement using a questionnaire The results of this study indicate that formal reasoning and achievement motivation have a strong relationship with student achievement, with each sig. (2-tailed) 0.02 between formal reasoning and learning achievement, so that 0.020.05 is smaller than the r table, which means there is a correlation between formal reasoning and learning achievement. As for learning motivation and learning achievement, the sig. (2-tailed), namely 0.02 0.05, means there is a correlation between learning motivation and learning achievement. From these results, formal reasoning allows individuals to think logically and systematically, while achievement motivation encourages academic success. The two mutually reinforce and enhance each other, creating a productive learning environment and enhancing overall individual achievement.